2022
DOI: 10.21608/ejz.2022.150510.1086
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Helminths of the Freshwater Catfish (Clarias Gariepinus) From Fayoum Governorate, Egypt

Abstract: The parasitic diseases are one of the potential factors that restrict the development of fish aquaculture because fish parasites not only can cause injuries, but can even lead to death of the fish. The present study aimed to record/update the prevalence and intensity of parasitic helminths in the freshwater catfish "Clarias gariepinus " in Fyoum Governorate, Egypt. A total of 368 Clarias gariepinus samples were collected from Bahr Youssef (line of the River Nile) from Fayoum Governorate during the period from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In other instances, protruding spicules were serendipitously studied using scanning electron microscopy (SEM) (e.g. Moravec & Jirků, 2017; Moravec & Scholz, 2017; Rindoria et al , 2020; Al-Bassel et al , 2022) and these studies revealed additional detail. On rare occasions, spicules were isolated through dissection from the spicule pouch of specimens in glycerine or lactic acid, which were then studied with SEM (Eisenback, 1985; Rammah & Hirschmann, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In other instances, protruding spicules were serendipitously studied using scanning electron microscopy (SEM) (e.g. Moravec & Jirků, 2017; Moravec & Scholz, 2017; Rindoria et al , 2020; Al-Bassel et al , 2022) and these studies revealed additional detail. On rare occasions, spicules were isolated through dissection from the spicule pouch of specimens in glycerine or lactic acid, which were then studied with SEM (Eisenback, 1985; Rammah & Hirschmann, 1987).…”
Section: Introductionmentioning
confidence: 99%